Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7570/jomes20008
|View full text |Cite
|
Sign up to set email alerts
|

Males with Obesity and Overweight

Abstract: Global average data suggest that the prevalence of obese and overweight males is much higher than that of females in some regions. The gender gap in obese and overweight individuals has deepened in many countries, and the gap is more prominent in overweight than in obesity. In particular, the prevalence of male obesity has continuously increased in the Republic of Korea over the past two decades, whereas the increase in female obesity has slowed and may even have plateaued. The cutoff point for obesity in Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 53 publications
2
28
1
8
Order By: Relevance
“…However, it was not concluded that there is a dependency between the frequency of water consumption and the age of the consumer (statistically important dependency was observed between the age of the consumer and the frequency of consumption: flavored water, fruit nectars, carbonated fruit beverages, carbonated beverages and energy as well as isotonic drinks). It was suggested that there is a much higher percentage of obese and overweight men than women in certain parts of the world such as e.g., China, Germany, France [ 33 ]. In the light of the mentioned research it should be a warning light for dietitians and health professionals because in this study men declared to consume water and other non-carbonated beverages more rarely as opposed to carbonated beverages of the ‘Coke’ type, fruit drinks or carbonated water.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not concluded that there is a dependency between the frequency of water consumption and the age of the consumer (statistically important dependency was observed between the age of the consumer and the frequency of consumption: flavored water, fruit nectars, carbonated fruit beverages, carbonated beverages and energy as well as isotonic drinks). It was suggested that there is a much higher percentage of obese and overweight men than women in certain parts of the world such as e.g., China, Germany, France [ 33 ]. In the light of the mentioned research it should be a warning light for dietitians and health professionals because in this study men declared to consume water and other non-carbonated beverages more rarely as opposed to carbonated beverages of the ‘Coke’ type, fruit drinks or carbonated water.…”
Section: Discussionmentioning
confidence: 99%
“…A more interesting fact to be furthermore researched in these patients suffering from lower limb OA with knee abnormalities comparable to our results is the importance of BMI in one's OA formation. It is important to underline since it was shown that men that lose weight tend to have a decreased opportunity of developing OA in their elderly years, but not so many findings emphasize which are the differences between the dominant and non-dominant lower limbs [64][65][66]. Females with hip OA (with or without knee OA) present important changes on the dominant limb, even though in literature it has been tried to see whether the dominance of the limb generates OA joint degenerations, or it is actually the disease that may cause differences between limbs, but a longitudinal examination needs approaching as well [67].…”
Section: Discussionmentioning
confidence: 99%
“…3 Resiko dampak obesitas terhadap fertilitas pada laki-laki lebih besar dibandingkan pada perempuan. Penelitian lain melaporkan semakin meningkat berat badan maka produksi testosteron kian menurun 4 .…”
Section: Pendahuluanunclassified